Learning to teach mathematics in the secondary school : a companion to school experience (New York : Routledge, 1999)
Mathematics education - who decides? Mathematics in the national curriculum. Pupils learning mathematics. Different teaching approaches. Planning for mathematics learning. Assessment and public examinations. Communicating mathematically. Using information and communications technology. Mainstream mathematics teaching and special educational needs. Getting the whole picture. Teaching mathematics post-16. Professional development.
Keywords: Mathematics; Mathematics -- Study and teaching (Secondary) -- United States